Forms Of Legal Protection In Timor Leste For Foreign Citizens Who Have Been Sentenced To Death in Their Country of Origin - Constantino Magno; Richard Alfred Xavier Da Conceicao; Elvira Dos Santos Afonso; Rogerio Menezes Da Costa; Reinaldo Fransisco Luis (CV. Ulil Albab Corp, 2025)
The purpose of this research is to find out